Influence motivation investment, literacy finance, and development technology to interest invest in students - Gatot Subiyakto; Novianti Alit Rahayu; Bertilia Lina Kusrina (Keynesia : International Journal of Economy and Business, 2022)
This study aims to determine the effect of investment motivation variables, financial literacy, and technological developments on investment interest in students of the Faculty of Economics, Gunadarma University. The analytical method used in this study is a quantitative method. Sources of data used are primary data obtained through questionnaires that have previously been distributed to respondents. Some of the test stages carried out are as follows: Validity Test, Reliability Test, Classic Assumption Test, t Test (Partial), F Test (Simultaneous), Linear Regression Analysis and Coefficient of Determination (R2). The data used is a questionnaire instrument, with valid data obtained as many as 100 respondents. The sampling method used in this research is purposive sampling where there are certain criteria in determining the sample. The tool used in the test is SPSS. The results of this study prove that simultaneously investment motivation, financial literacy, and technological developments have an effect on investment interest. While partially, only investment motivation has an effect on investment interest. However, it is different from financial literacy and technological developments which partially have no effect on investment interest.